Is fatigue all in your head? A critical review of the central governor model - Weir, J. P.; Beck, T. W.; Cramer, J. T.; Housh, T. J. (British Journal of Sports Medicine, 2006)
The central governor model has recently been proposed as a general model to explain the phenomenon of fatigue. It proposes that the subconscious brain regulates power output (pacing strategy) by modulating motor unit recruitment to preserve whole body homoeostasis and prevent catastrophic physiological failure such as rigor. In this model, the word fatigue is redefined from a term that describes an exercise decline in the ability to produce force and power to one of sensation or emotion. The underpinnings of the central governor model are the refutation of what is described variously as peripheral fatigue, limitations models, and the cardiovascular/anaerobic/catastrophe model. This argument centres on the inability of lactic acid models of fatigue to adequately explain fatigue. In this review, it is argued that a variety of peripheral factors other than lactic acid are known to compromise muscle force and power and that these effects may protect against "catastrophe". Further, it is shown that a variety of studies indicate that fatigue induced decreases in performance cannot be adequately explained by the central governor model. Instead, it is suggested that the concept of task dependency, in which the mechanisms of fatigue vary depending on the specific exercise stressor, is a more comprehensive and defensible model of fatigue. This model includes aspects of both central and peripheral contributions to fatigue, and the relative importance of each probably varies with the type of exercise.